The Properties of A Full–Fledged Reading Ability (Correctness, Consciousness, Expressiveness, Fluency) and the Approach of Improvement - Madaminova Samidabonu Umidovna (International Journal on Orange Technologies, 2021)
In this article, you will be able to consider such topical topics as what is the "reading skill", what stages are divided into . What mistakes students make when reading, how to correctly correct mistakes without interrupting the reader. Reading as a basic element. Formation of readers ' interests. Reading skills are correctness, fluency, consciousness, expressiveness. The stages of reading formation are analytical, synthetic, and automation.